Chremistica ribhoi sp. n. (Hemiptera: Cicadidae) from North-East India and its mass emergence - Hajong, Sudhanya Ray; Yaakop, Salmah (Zootaxa, 2013)
The genus Chremistica Stål, 1870 is reported from the northeastern region of India for the first time. A new species, Chremistica  ribhoi, is described from this region and male genitalia illustrations and scanning electron microscope photographs of the pygofer for C. ribhoi are presented. Observations on mass emergence of C. ribhoi are described.